ReBEc 2.0: rumo a uma nova plataforma para dados científicos - Silva, Luiza Rosângela da; Laguardia, Josué; Tostes, Diego Gomes; Ribeiro, Alexandre Moretto; Ribeiro, Carlos Eduardo; Matte, Lia C.; Lima, Vanessa; Alves, Marcelo Rodrigo d’Avelar Bastos; Eiras, Daniel Pereira; Maturana, Giancarlo; Lima, Eduardo Alves C. (Cadernos BAD, 2014)
ReBEc 2.0: rumo a uma nova plataforma para dados científicos